HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PRAKTIK KESEHATAN REPRODUKSI SISWA DI SMK “X” KABUPATEN KEBUMEN TRIWULAN I TAHUN 2016 - Zakia Ulfah; Djoko Nugroho; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Adolescent problems related to reproduction health is often caused by lack of information, understanding and awareness affecting in some problems faced by teenagers. In SMK “X” Kebumen, there are one to two cases of unwanted pregnancies among the students in almost every year. The aim of this research is to analyze the relation between knowledge and attitude toward reproduction health practices of students in SMK “X” Kebumen. This research is explanatory research with cross sectional study. The population is the entire students of Class X and XI with 610 students in total and the sample is 100 students chosen with simple random sampling technique. The analysis is done using univariate, bivariate analysis (Spearman rank) and multivariate (Multiple Linear Regression) analysis. Value significance relationship using significant value of α = 5%. The results of univariate analysis shows the largest percentage of students lack knowledge of reproductive health (57.0%), the juvenile hormones knowledge about KNPI (Kissing, patting, necking and intercourse); reproductive health attitudes enough students (74.0%) on the attitude of students agreed on frequent sexual intercourse caused by watching porn and the percentage of students sufficient reproductive health practices (54.0%) on the practice of students about watching porn, holding hands tenderly, kiss and hugging intimate with the opposite sex and doing masturbation, intimate stimulation in the neck area, and touched intimate breast area.The result of bivariat analysis shows that there is significant relation between student reproduction health knowledge toward its practice (p value=0,0001; 95%; r=0,664; CI=0,568-0,768); there is significant relation between student reproduction health attitude toward its practice (p value =0,0001; r=0,745; 95%; CI=0,634-0,828). The result of multivariat analysis shows that there is significant relation between knowledge and attitude towards student reproduction health practice (p value=0,0001; y=17,165 + 0,398 X1 + 0,337 X2). Based on those results, it is suggested to maximize the learning with the depth of the material, the use of instructional time with inovative methods such as video playback, role playing and group discussion, and peer companion.